Implementasi Metode Analytical Hierarchy Process (AHP) Menentukan Karyawan Terbaik Pada CV. Diana Kosmetik Bandung - Senna Hendrian (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Increasing the productivity of an agency's performance is inseparable from the quality of human resources (HR) who are reliable, professional and have high integrity. Increasing the competence or expertise of HR can support an increase in employee performance. Managing employee performance effectively is one of the key factors to improve the company's business performance. In this case, effective performance management includes the process of measuring employee performance objectively through a series of appropriate performance indicators. The problems that have been the inhibiting factors are 1) the process of determining the best employees still uses conventional methods, so errors often occur in evaluating employee performance, 2) there is no system or method that can quickly, precisely and accurately determine the best employees at CV Diana Cosmetics Bandung, so as to produce reports that are more organized, so that they can be used as a reference for future elections. Implementation of the Analytical Hierarchy Process (AHP) Method for Determining the Best Employees at CV. Diana Cosmetics Bandung is the right method to use so that the final result can be obtained by multiplying the priority criteria value with the priority value of the sub criteria according to the Employee value data, for example the value "0.17" in the discipline column row A results from "0.41" ( obtained from the sufficient value of employee A, the priority of the sub criteria is sufficient on discipline) multiplied by the priority of the disciplinary criteria "0.42".